2004
DOI: 10.1016/j.ejcts.2004.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pre-emptive milrinone in off-pump coronary artery bypass surgery: comparison between patients with a low and normal pre-graft cardiac index

Abstract: Pre-emptive milrinone infusion without bolus effectively improved cardiac performance during OPCAB and was especially useful for patients with low pre-graft cardiac index to prevent the decrease in cardiac index and stroke volume index below the critical level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Of these, the most common reasons for exclusion were as follows: valid data could not be obtained by the authors (87 studies), milrinone was compared with other drugs (17 studies), pediatric populations were used (11 studies), studies were nonrandomized controlled trials (9 studies), crossover studies (5 studies), studies published as abstracts only (4 studies), studies used mechanical devices as controls (4 studies), studies used inhaled milrinone (3 studies), studies used randomization of brain-dead organ donors (3 studies), studies were animal studies (2 studies), and studies used healthy volunteers (1 study). Ultimately, sixteen randomized clinical trials were assessed in compliance with the inclusion criteria (Table 1) [31,[38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, the most common reasons for exclusion were as follows: valid data could not be obtained by the authors (87 studies), milrinone was compared with other drugs (17 studies), pediatric populations were used (11 studies), studies were nonrandomized controlled trials (9 studies), crossover studies (5 studies), studies published as abstracts only (4 studies), studies used mechanical devices as controls (4 studies), studies used inhaled milrinone (3 studies), studies used randomization of brain-dead organ donors (3 studies), studies were animal studies (2 studies), and studies used healthy volunteers (1 study). Ultimately, sixteen randomized clinical trials were assessed in compliance with the inclusion criteria (Table 1) [31,[38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Resultsmentioning
confidence: 99%
“…The total number of patients in the 16 included trials was 698, who underwent CABG surgery (346 treated with placebo/standard care and 352 treated with milrinone) ( Table 2 and Table 3). In ve of these studies, off-pump CABG surgery was performed [31,41,45,46,49], and on-pump CABG surgery was performed in 11 studies [39-45, 48, 49, 51, 52]. As the result showed, the mortality of on-pump CABG between milrinone treatment and placebo/standard care groups, the occurrence was [5/139 (3.59 %) vs. 4/146 (2.74 %), odds ratio (OR) = 1.17 (0.37-3.72), p value = 0.649, I-squared = 0.0%].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Previous studies on patients who are undergoing OPCAB demonstrated that milrinone infusion was beneficial to minimize the decrease of the CI and SvO 2 [11,12]. It was also suggested that milrinone might improve the ventricular diastolic function in patients with congestive heart failure since ventricular relaxation, as well as contraction, is an energy-dependent process [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The patient is commenced on low-mid-dose (0.2-0.4 g/kg/min) intravenous milrinone, without a loading dose, after induction of anaesthesia. This has a two-fold benefit in increasing cardiac output for endorgan perfusion [14] and as a systemic vasodilator when using all arterial grafts [15]. Avoiding a loading dose of milrinone may reduce haemodynamic instability [16].…”
Section: Anaesthetic Considerationsmentioning
confidence: 99%